2005
DOI: 10.4141/p04-158
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and tactics for herbicide use reduction in field crops in Canada: A review

Abstract: There are many economic and health reasons for reducing pesticide use in Canada. Herbicide use on field crops is by far the most common pesticide use in Canada. This paper is a review of four topics related to herbicide use reduction on field crops in Canada: (1) broad strategies and (2) specific tactics for herbicide use reduction; (3) factors affecting adoption; and 4) research approaches for improving the implementation of herbicide use reduction. Numerous tactics exist to use herbicides more efficiently an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 227 publications
0
51
0
6
Order By: Relevance
“…Nesse aspecto, muitas vezes, com a integração de práticas de manejo, as doses de herbicidas podem ser reduzidas e, ainda assim, prover controle satisfatório dessas plantas (Mohler, 2001;Nazarko et al, 2005). Uma prática importante a considerar na adoção do manejo cultural de plantas daninhas refere-se à redução do espaçamento entre fileiras da cultura.…”
Section: Introductionunclassified
“…Nesse aspecto, muitas vezes, com a integração de práticas de manejo, as doses de herbicidas podem ser reduzidas e, ainda assim, prover controle satisfatório dessas plantas (Mohler, 2001;Nazarko et al, 2005). Uma prática importante a considerar na adoção do manejo cultural de plantas daninhas refere-se à redução do espaçamento entre fileiras da cultura.…”
Section: Introductionunclassified
“…Increasing seeding rates has been shown to be an effective strategy for enhancing crop competitiveness in integrated weed management systems [39,40], or other reduced input systems aiming to decrease herbicide use [41]. O'Donovan et al [42], found that increasing barley crop densities enhanced the effectiveness of the herbicide tralkoxydim on wild oats, allowing for reduced application rates.…”
Section: Weed Managementmentioning
confidence: 99%
“…[35,43] Several studies have demonstrated that this tactic can maintain effective weed control and sustain economically acceptable crop yields. [44,45] Conflicting results regarding success in using reduced herbicide rates may be due to a variety of factors such as spray volume, droplet size, adjuvants, temperature, humidity, light quality, soil moisture content, weed size and weed species.…”
Section: Herbicide-based Tacticsmentioning
confidence: 99%
“…tank mixes of postemergence herbicides with different modes of action). [35,41] Therefore, the choice of suitable herbicides should also take into account other factors affecting weed resistance evolution such as the frequency, number, dominance and fitness of genes conferring resistance to an herbicide.…”
Section: Herbicide-based Tacticsmentioning
confidence: 99%
See 1 more Smart Citation